2014
DOI: 10.1371/journal.ppat.1004033
|View full text |Cite
|
Sign up to set email alerts
|

An Immunomics Approach to Schistosome Antigen Discovery: Antibody Signatures of Naturally Resistant and Chronically Infected Individuals from Endemic Areas

Abstract: Schistosomiasis is a neglected tropical disease that is responsible for almost 300,000 deaths annually. Mass drug administration (MDA) is used worldwide for the control of schistosomiasis, but chemotherapy fails to prevent reinfection with schistosomes, so MDA alone is not sufficient to eliminate the disease, and a prophylactic vaccine is required. Herein, we take advantage of recent advances in systems biology and longitudinal studies in schistosomiasis endemic areas in Brazil to pilot an immunomics approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
78
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(78 citation statements)
references
References 81 publications
0
78
0
Order By: Relevance
“…Using an immunomic approach (4850), we profiled host antibody responses to a subset of parasite stage-specific proteins (397 proteins). These selected proteins (https://exon.niaid.nih.gov/transcriptome/O_volvulus/Additional_file_14.xlsx) were printed on a protein array, quality checked, and assessed for isotype-specific antibody responses (IgG1, IgG3, IgG4, and IgE) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Using an immunomic approach (4850), we profiled host antibody responses to a subset of parasite stage-specific proteins (397 proteins). These selected proteins (https://exon.niaid.nih.gov/transcriptome/O_volvulus/Additional_file_14.xlsx) were printed on a protein array, quality checked, and assessed for isotype-specific antibody responses (IgG1, IgG3, IgG4, and IgE) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These include the tetraspanin SmTSP-2, the tegumental antigen Sm29, and the very low-density lipoprotein-binding protein SjSVLBP as well as other novel proteins (reviewed in (McWilliam et al 2012). More recently, these protein microarrays have been screened for IgE and multiple IgG subclasses responses using sera from resistant or susceptible individuals (Gaze et al 2014). The resultant antibody profiles could distinguish between protected vs non-protected cohorts and allowed identification of antigens that might represent excellent vaccine candidates (Gaze et al 2014).…”
Section: Immunomics Of Parasitesmentioning
confidence: 99%
“…Human correlate studies revealed Sm-p80-reactivity with IgG in human sera from individuals that are naturally resistant to schistosome infection [48]. Equally important is the absence of prevailing Sm-p80-specific IgE in a high risk/infected populations, thus minimizing the risk of hypersensitivity reaction following vaccination with Sm-p80 in humans [48;54]. It is noteworthy that the Sm-p80 vaccine has also been demonstrated to offer cross-species protection against S. haematobium infections in hamsters and baboons [55] as well as against S. japonicum infections in mice [25;56].…”
Section: Introductionmentioning
confidence: 99%